The legal status and rights of the victim in a plea bargain according to the criminal procedural legislation of the Republic of Kazakhstan - Nurgaliyev, B.M.; Ualiyev, K.S.; Kussainova, А.K. (KSU Publ., 2018)
The article is devoted to the legal status of the victim (civil plaintiff) in the procedural agreement on the criminal procedural legislation of the Republic of Kazakhstan. The procedure for concluding procedural agreements in the form of a plea bargain and the role of the victim and civil plaintiff in concluding this procedural action are considered. Unfortunately, the rights of the victim and civil plaintiff were not regulated in detail in the Kazakhstani CPC until now, when they considered the request for a plea bargain, they were not warned about procedural and other problematic issues arising in the preparation of such agreements. And they are worried not only material, but also moral claims, and how they are resolved in the course of preliminary investigation and further in court. As you know, the developers at the stage of project development had a dilemma - to include the victim in the «transaction» orbit, or not. Now this problem is solved in the new Kazakhstani legislation. The role of the injured party in conciliation proceedings under the legislation of foreign countries is shown, where a civil claim for damages is also not included in the «deal» in most of the jurisdictions. The practice of considering criminal cases in conciliation proceedings in Kazakhstani courts is analyzed, procedural issues affecting the legality and validity of final decisions are emphasized. Arguments of imperfection of some procedural norms and difficulties in judicial consideration of this category of criminal cases are given.
Қазақстан Республикасының қылмыстық-процессуалдық іс жүргізу заңнамасы бойынша кінəні мойындау туралы мəміледегі жəбірленушінің құқықтық мəртебесі мен құқықтары
Правовое положение и права потерпевшего в сделке о признании вины по уголовно-процессуальному законодательству Республики Казахстан
Keywords: Criminal process; legal proceedings; procedural agreement; a plea bargain; victim; civil plaintiff